Expressive use of punctuation marks in the novel "The Moon and Sixpence" - , Dilyara B. Garifullina, Milyausha R. Garaeva, Alsu Yu. Giniyatullina, Ildar G. Ahmetzy (Opción, 2019)
The present study aims to investigate expressive use of punctuation marks in the novel “The Moon and Sixpence” by Somerset Maugham. The principle method of the research involves that of linguistic description, including observation, interpretation and the contextual analysis. The present paper aims to investigate the concept of expressive punctuation, and revealing the main emotive punctuation marks in the novel "The Moon and Sixpence" by SomersetMaugham. The results of the present study can be used in developing materials for EFL learners, which can be a facilitative factor to raise the learners’ awareness.